2016
DOI: 10.1016/j.ensci.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice concerning swallowing disorders in hemiplegic patients among nurses of Bobo–Dioulasso urban primary health care centers in Burkina Faso

Abstract: IntroductionThe quality of management of swallowing disorders (SD) from admission onwards influences the patients' nutritional status and their prognosis. Neurological diseases are the main causes of SD, affecting one in three patients with hemiplegia (Hp). In Burkina Faso (BF), primary health care center (PHCC) nurses are the first to manage these patients, but there are no data related to their management of SD. The study aimed to assess knowledge and practices regarding SD in Hp among PHCC nurses in Bobo–Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…The personal system barriers identified as deficiencies in knowledge, skills and attitudes can significantly affect the standard of care provided to persons with stroke who present with communication difficulties and dysphagia. There was a consistent lack of familiarity with SLT terminology found across the three studies, which is congruent with findings in the current literature (Albini et al 2013;Diendéré et al 2016; Dziewas et al Familiarity with terms such as 'dysphagia' could be because of increased exposure to the condition, and its related terms in the workplace, as other healthcare professionals such as medical doctors might use similar terminology during interaction with nurses. Dysphagia terminology might also be perceived as important, as inadequate management of dysphagia could contribute to life-threatening complications, whilst poor knowledge of communication terminology does not generally pose a risk to patients' physical health.…”
Section: Personal System Barrierssupporting
confidence: 86%
See 1 more Smart Citation
“…The personal system barriers identified as deficiencies in knowledge, skills and attitudes can significantly affect the standard of care provided to persons with stroke who present with communication difficulties and dysphagia. There was a consistent lack of familiarity with SLT terminology found across the three studies, which is congruent with findings in the current literature (Albini et al 2013;Diendéré et al 2016; Dziewas et al Familiarity with terms such as 'dysphagia' could be because of increased exposure to the condition, and its related terms in the workplace, as other healthcare professionals such as medical doctors might use similar terminology during interaction with nurses. Dysphagia terminology might also be perceived as important, as inadequate management of dysphagia could contribute to life-threatening complications, whilst poor knowledge of communication terminology does not generally pose a risk to patients' physical health.…”
Section: Personal System Barrierssupporting
confidence: 86%
“…Research has identified a lack of nurses' knowledge regarding best practices for the rehabilitation of persons with stroke, as well as lack of knowledge regarding SLT diagnoses and terminology. This is supported by international research (Albini et al 2013;Diendéré et al 2016;Dziewas et al 2017;Wang, Lu & Chang 2014) and African research (Rhoda & Pickel-Voigt 2015). Furthermore, issues of nurses disagreeing with SLT recommendations (Hadely, Power & O-Halloran 2014) and their feelings of inadequacy when working with patients with communication or dysphagia diagnoses (McGinnis et al 2019;Smith et al 2015) have been identified.…”
Section: Personal Systemsmentioning
confidence: 99%
“…Several researchers have described registered nurses competency in term of knowledge and skills regarding screening dysphagia [30, 31, 35, 38, 39]. McHale, Phipps, Horvath, Schmelz, (1998) conducted a study to describe the practical knowledge of expert twelve nurses.…”
Section: Resultsmentioning
confidence: 99%
“…They found that few nurses understood the importance of screening dysphagia [38]. In order to improve care among stroke patients, Diendéré, et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation